Employment Recovery in Europe and Central Asia - Koettl, Johannes; Oral, Isil; Santos, Indhira (World Bank, Washington, DC, 2012)
Despite high unemployment in most Eastern Europe and Central Asia (ECA) countries, people have not withdrawn from the labor market but continue to actively look for jobs. Unemployment increased significantly in ECA countries during the crisis, particularly among youth. However, young people are also the ones benefiting most from the recovery. Labor market recovery remained sluggish up to the third quarter of 2010. Many countries have seen only a slight recovery in unemployment rates, although output is recovering everywhere. Up to the third quarter of 2010, the Gross Domestic Product (GDP) upturn in most ECA countries appeared to be driven by increases in productivity and hours worked; however, these are still below pre-crisis levels. This suggests that there is room in most countries for further increases in productivity and hours worked, which could delay the recovery in employment.